Concepts and reality in the history of philosophy : tracing a philosophical error from Locke to Bradley - Ellis, Fiona, 1964- (Routledge advances in the history of philosophy, 2005)
"There are unacceptable metaphysical presuppositions at the heart of the epistemology of Locke, Berkeley, Nietzsche, and Kant. This controversial claim is laid out and explained in this book." "Transcending the division between 'continental' and 'analytical' philosophy, Fiona Ellis shows how Hegel offers a way out of this philosophical error. This is a book which will interest all scholars of the history of philosophy."--Jacket